Posttraumatic Growth in Psychosis - Mazor, Yael; Gelkopf, Marc; Mueser, Kim T.; Roe, David (Frontiers in Psychiatry, 2016)
Objective: Recent research has shown high rates of exposure to trauma among people with serious mental illness (SMI). In addition studies suggest that psychosis and mental illness-related experiences can be extremely traumatic. While some individuals develop full blown PTSD related to these experiences, it has been noted that some may also experience posttraumatic growth (PTG). However, few studies have examined PTG as a possible outcome in people who have experienced psychosis. Method: To further understand the relationships between psychosis and PTG, 121 participants were recruited from community mental health rehabilitation centers and administered trauma and psychiatric questionnaires. Results: High levels of traumatic exposure were found in the sample. Regarding our main focus of study we observed that people who endured psychosis can experience PTG, and that PTG is mediated by meaning making and coping self-efficacy appraisal. Psychotic symptoms were found to be a major obstacle to meaning making, coping self-efficacy, and PTG, whereas negative symptoms were found to be significantly related to PTG when mediated by meaning making and coping self-efficacy. Conclusion: The current research provides preliminary evidence for potential role of meaning making and coping self-efficacy as mediators of PTG in the clinical, highly traumatized population of people with SMI who have experienced psychosis. This may have both research as well as clinical practice relevance for the field of psychiatric rehabilitation.